Personifikacja Aeternitas na monetach rzymskich propagujących ideę wieczności cesarza - Balbuza, Katarzyna (Poznańskie Towarzystwo Przyjaciół Nauk, 2013)
The paper analyzes the typology of imagery of Aeternitas in the coinage (from Vespasian to the Tetrarchy) propagating the concept of emperor’s eternity. The iconography of Aeternitas is not homogenous, being characterised by an abundance and diversity of motifs and representations. One thing that would not change, a common denominator of sorts, was the figure of a woman in a long dress. Her attributes, how- ever, did fluctuate and depending on their kind symbolised either cosmic eternity or renewable time (phoenix). Aeternitas personified by a woman in long dress, shown in contrapposto, holding a radiant sun and moon was introduced on the reverses of coins in the Flavian period and continued to appear until Hadrian. During that time, the astral attributes would be exchanged for other devices, but although these insignia changed over time, the figure in a long tunic remained, as a permanent and originally Roman element in the iconography of female personifications of the Roman Empire.
Summary The iconography of Aeternitas in Roman coinage is not homogenous, being char- acterised by an abundance and diversity of motifs and representations. Still, one thing they always had in common was a figure of woman in a long dress, equipped with various attributes associated with the symbolic of cosmic eternity or renewable time (phoenix). Aeternitas personified by a woman in a long dress, shown in contrapposto, holding a radiant sun and moon entered the extensive stock of personified Roman abstractions thanks to the Flavians. Although her insignia changed over time, the figure in a long tunic would remain, as a permanent and originally Roman element in the iconography of female personifications.
Keywords: iconography; Aeternitas Augusti; Roman numismatics; ideology